Herding behavior and information effect of firm's ownership - Mohd Nasarudin, Ahmad Fawwaz; Hanijito, Agus; Amin Noordin, Bany Ariffin; Matemilola, B. T. (The Empirical Economics Letters, 2017)
Following study on macro information on investor’s herding decision by Galariotis et al. (2014), this study question the importance of information dissemination at firm’s level 0n investor’s herding decision. By categorizing firms according to family and non-family ownership, the cross sectional absolute deviation (CSAD) was employed to test the herding existence in 22 different countries. The findings suggest limited herding activity as only Greece, New Zealand and China reported for herding during the study period. As for the conclusion, the study proves that investor do not place high importance on firm’s information dissemination management as relatives to the market announcement.